(untitled) (Journal of science and technology exploration, 2026)
This paper aims to conduct a systematic philosophical reflection and critical analysis of the increasingly prevalent digital wave in the field of dance education. Moving beyond mere praise for the efficiency of technological tools, it delves into the profound impact of digitalization on authentic dance experiences and teaching ethics. Grounded in the dual theoretical frameworks of technological phenomenology and epistemology of the body, the study seeks to reveal how mainstream digital technologies—such as motion capture, virtual reality, and artificial intelligence—systematically simplify and reconstruct the continuous, emotionally rich, and intentional bodily practice of dance into a collection of discrete, quantifiable, and computable movement parameters through their inherent "data-driven" operational paradigms. The core argument of this paper is that this fundamental process of "dimensional reduction" leads to the loss of essential emotional texture, spontaneous creativity, and cultural significance in dance, effectively "obscuring" the ontological essence of dance. To substantiate this claim, the study extensively draws upon and expands Michael Polanyi’s classic theory of "tacit knowledge," eloquently demonstrating that the "kinesthetic intelligence" at the heart of dance, the "vital rhythm" generated within specific cultural contexts, and the "instantaneous ethical choices" embedded in live improvisation all ontologically resist complete formalization and computational modeling by existing algorithmic frameworks. The critique presented here does not aim to negate technology per se but rather advocates for a fundamental shift in the perception of technology: from an instrumental rationality focused on "monitoring" and "replacing" the body to an "embodied-augmentation" paradigm that views technology as an "extension of the body" and an "amplifier of perception." The ethical mission of future dance education technology should be to deepen and expand the experiential dimensions of the body and foster more profound intersubjective interactions, rather than simplifying or disciplining the body. Ultimately, this study calls for the establishment of an ontological value-ethical framework centered on the body in the design, application, and evaluation of dance education technology, ensuring that technological progress consistently serves the generation of artistic aura and the holistic development of individuals, rather than undermining them.